تعدد الزوجات وأثره في ضوء القرآن والسنة المجتمع الإماراتي أنموذجا - كندي، علي سيف محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The research tackles the Emirates social status through study, induction and writings, using statistics and questionnaires on one of the most important contemporary social issues. This research aims to find appropriate solutions in order to put an end to the so-called “The phenomenon of spinsterhood” and the unbalance in population and demographic mix of the Emirates society that makes it suffers. Also, the research implants the principle of polygamy to be adapted by men and accepted by women. The researcher highlights the idea of polygamy in an acceptable way to be a good solution for the society's problem. The research methods are adapted through observing and following up the Emirates social status. The matter of researching is completed through observing references and statistics that had been done before by the Research Centers in the country (UAE), and allocating the rates through the questionnaires examined by the specialists. The study is culminated into a group of outcomes: most importantly, the increasing rate of the phenomenon of spinsterhood and the number of divorced women in Emirates society to limit it by making Polygamy as one of accepted solutions. It is necessary to start an awareness movement by the non-governmental organizations NGO's and official authorities in order to spread the culture of marriage, establishing Psychological and family guidance centers. In addition, parents are educated with the Islamic culture to accept the idea of polygamy and to give the ultimate priority to the care of the spinsters and female divorcee.